Hiding in Plain Sight: Observations from a Review of Positive Urine Cultures Prior to an Antimicrobial Stewardship Program Campaign Targeting Asymptomatic Bacteriuria. (4th October 2017) - Williamson, Julie E; Logan, Andrea Y; Reinke, Emily K; Jarrett, Steven; Davidson, Lisa E
Abstract: Background: Data have shown that many patients with asymptomatic bacteriuria (ASB) receive unnecessary antibiotics, increasing risk of adverse events and resistance. Positive urine culture (PUC) and urinalysis (UA) results have been shown to prompt treatment without symptoms or compelling indication (pregnancy or prior to urologic procedure). We reviewed clinician action based on PUCs across 28 acute-care hospitals of varied size, scope, and antimicrobial stewardship program (ASP) maturity prior to an ASB educational campaign. Methods: We conducted a retrospective sampling of inpatient PUCs collected February 1– 28, 2017. Patients were excluded if: pregnant, undergoing urologic procedure, aged < 18 years, neutropenic, or were admitted on active urinary tract infection (UTI) therapy or with nephrolithiasis. A CDC UTI assessment form was adapted to collect: demographic, clinical, and laboratory data, The presence of UTI symptoms, microbiological results, antimicrobial therapy and duration, and rate of ASP intervention. Results: Data from the First 200 included patients at 14 hospitals are shown. Most patients (84/200 (42%)) presented with only non-specific symptoms (NSS) or no symptoms (62/200 (31%)) vs. (vs) at least 1 specific urinary symptom (SUS) (54 / 200 (27%)). Ceftriaxone was the most common empiric therapy in those with no symptoms (17/40(42.5%)) or NSS (35/74(47%)) who were treated. Interventions were documented on 18/200 (9%) patients, despite daily use of clinical decision support (CDS) at 58% of hospitals. Conclusion: ASB presents many targets and challenges. UA and UC were often performed in patients with no symptoms or NSS. Thus, optimal ordering of UA and UC should be targeted to avoid unnecessary cost and therapy. Treatment of patients with no symptoms appeared to be more common in rural vs. urban hospitals and may help focus education. Low ASP intervention rates, despite use of CDS, may indicate challenges in identifying ASB patients. Many patients received ceftriaxone, which may not be targeted for initial review by ASP. Due to high volume at many sites, daily review of all PUCs may not be feasible. Disclosures: All authors: No reported disclosures.